PELATIHAN PENERAPAN SARANA FISIK MATERI PEMBELAJARAN BAGI GURU DI SDN KOTA DEPOK - Rina Nur Hidayati; Isroyati Isroyati (Abdimas Siliwangi, 2020)
This community service aims to provide training to teaching staff at the Ratu Jaya 3 State Elementary School (SDN) in Depok City regarding variations in the learning process, due to the existence and the important role of an educator as a learning facilitator for students. The application of instructional media is also referred to as one of the physical means or intermediaries used in the process of interaction that takes place between the teacher and students to encourage the occurrence of teaching and learning with the aim of gaining knowledge, skills and strengthening what is learned and helps to achieve quality learning goals. The implementation of community service uses several methods, namely, presentation, discussion of teaching demonstration and evaluation. This training is given to participants to get references on creative, innovative and fun learning that can be used in the learning process. Of all the results obtained by the participants from community service activities, this will certainly improve the competence of teachers in teaching.